Educational Documents England and Wales: 1816 to the present day - Geraldina Porto Witter (Revista de História, 1977)
MACLURE, J. Stuart. Educational Documents England and Wales: 1816 to the present day. 3a edição 1973. London: Methuen & Co. Ltd.